Posterior reversible encephalopathy syndrome during epidural labor analgesia: a case report - Sadamu Sugimoto; Misako Shimizu; Mariko Takebe; Kousou Matsuura; Tomonori Takazawa (JA Clinical Reports)
Abstract Background Posterior reversible encephalopathy syndrome (PRES) often presents with a wide range of neurological symptoms, and atypical manifestations can complicate its diagnosis. We report a rare case of peripartum PRES presenting with profound transient retrograde amnesia and orofacial automatisms, notably in the absence of generalized seizures. Case presentation A 29-year-old primigravida developed sustained hypertension during labor. Immediately postpartum, she experienced visual disturbances, followed by altered consciousness and lip-smacking movements. She subsequently developed profound but transient retrograde amnesia, including loss of autobiographical memory. Brain magnetic resonance imaging (MRI) revealed characteristic findings of PRES in the bilateral parieto-occipital lobes, leading to a diagnosis of PRES secondary to preeclampsia. Discussion This case highlights that peripartum PRES can present with atypical neurological symptoms, such as transient global amnesia and facial automatisms, even in the absence of typical eclamptic seizures. Such presentations warrant a high index of suspicion and prompt brain MRI to ensure accurate diagnosis and timely intervention.